Weight management and the wellness economy: structural implications for public health, prevention policies and health system sustainability - Serra, Federico; Ricciardi, Walter; Signorelli, Carlo; Siliquini, Roberta; Capolongo, Stefano; Cricelli, Claudio; Novelli, Giuseppe; Parisi, Attilio; Colao, Annamaria; Lenzi, Andrea (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: The rapid expansion of the global wellness economy represents one of the most profound structural transformations in contemporary health-related systems. Within this evolving landscape, weight management has shifted from an individual behavioral concern to a systems-level determinant of public health, deeply interconnected with non-communicable diseases (NCDs), environmental exposures, urban design, social inequities and health system sustainability. This work aims to analyze weight management as a structural infrastructure of preventive health policy embedded within the broader economic and governance architecture of the wellness economy. Methods: We conducted a multidisciplinary analysis drawing on literature published between 2010 and 2024, macroeconomic analyses and international policy frameworks. We examined weight management through a systems lens integrating environmental epigenetics, urban health, pharmacological innovation and planetary health governance. Results: The wellness economy currently exceeds USD 6.8 trillion globally and offers unprecedented preventive potential. However, it also risks fragmentation, inequity and over-medicalization if not aligned with public health principles. Our analysis demonstrates that obesity and metabolic risk must be reframed as structural determinants requiring regulatory alignment, environmental risk mitigation, equity safeguards and integration across public and private actors. Conclusions: Weight management should be recognized as a core component of health system resilience and long-term sustainability. Repositioning weight management as a structural determinant of planetary health represents a necessary paradigm shift for 21st-century prevention strategies. Effective governance requires coordinated action across multiple sectors to ensure equitable access and sustainable implementation.